Strategi Akomodasi Komunikasi dalam Proses Pembelajaran Secara Daring Selama Masa Pandemi Covid-19 - Astrid Kusuma Rahardaya; Irwansyah Irwansyah (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
This study aims to determine the communication accommodation strategy in the online learning process during the Covid-19 pandemic which occurred in teaching and learning activities in English at the elementary, junior high, senior high school and vocational school levels in Jakarta and also to determine the obstacles in communication accommodation strategies in the learning process. This study uses an exploratory method with Communication Accommodation Theory as a reference for data analysis used to discuss the possibility of a new phenomenon that has not been found in previous research and to examine phenomena in the context of real life. The results showed that the convergence strategy in communication accommodation in the online learning process during the Covid-19 pandemic was mostly carried out by English teachers at the SD, SMP, SMA, and SMK levels. This is to show that the teaching and learning delivery process is easier for students to understand and accept during online learning. In addition, based on the results of the interview, the researcher found that there were obstacles and impacts that were felt in the teaching and learning process taking place. Students tend to be passive compared to face-to-face learning.